Adamstown Gospel Chapel 75th anniversary, 1908-1983 : a commemorative booklet of our history - Adamstown Gospel Chapel (Adamstown, NSW Adamstown Gospel Chapel, 1983)
Includes photos.
Keywords: Brethren movement -- Australia -- history; Adamstown Gospel Chapel -- history